Bolshoi confidential secrets of the Russian ballet from the rule of the tsars to today - Morrison, Simon Alexander 1964- (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2016)
A history of the Bolshoi Ballet from its dubious beginnings in 1776 to the present, exploring its political ties and importance under various Russian regimes and how it came to define both Russian culture and ballet itself